Clinical advancement of precision theranostics in prostate cancer - Tan, Yue; Fang, Zhihui; Tang, Yongxiang; Liu, Kai; Zhao, Hong (Frontiers in Oncology, 2023)
Theranostic approaches with positron emission tomography/computed tomography (PET/CT) or PET/magnetic resonance imaging (PET/MRI) molecular imaging probes are being implemented clinically in prostate cancer (PCa) diagnosis and imaging-guided precision surgery. This review article provides a comprehensive summary of the rapidly expanding list of molecular imaging probes in this field, including their applications in early diagnosis of primary prostate lesions; detection of lymph node, skeletal and visceral metastases in biochemical relapsed patients; and intraoperative guidance for tumor margin detection and nerve preservation. Although each imaging probe shows preferred efficacy in some applications and limitations in others, the exploration and research efforts in this field will eventually lead to improved precision theranostics of PCa.